Halk Pazarı Ortamında Alıcı ve Satıcı Davranışları ve Karşılıklı Uygulanan Pazar Stratejileri Üzerine Nitel Bir Araştırma - Özüdoğru, Mesut; Ar, Aybeniz Akdeniz (Muş Alparslan Üniversitesi, 2018)
The aim of this study is to determine dealer and customer behaviours during the trade and mutual bazaar strategies used in the bazaar. With this purpose, face to face interview was conducted with 10 dealers and 5 men and 5 women totally 10 customers at two open-air public bazaars and one covered public bazaar in Bandırma in Balıkesir. A qualitative phenomenological model was used in this study. Research data was acquired using by semi-structered interview form improved by the authors. According to research results, it has been determined that dealers have cared stall appearance, communication, their own appearance and their own behaviour to attract the customers. In addition, it has been determined that the reasons why customers preferred bazaar are cheaper and fresher product, availability of bargain and product range. Customers complained about dealers mixing decay and fresh products and differences between front of and back of stall.

Bu çalışmanınamacı pazar ortamında alıcı ve satıcının alışveriş esnasındaki davranışları vepazarda uygulanan stratejileri tespit etmektir. Bu amaçla, Balıkesir’inBandırma ilçesinde kurulan 2 açık 1 kapalı olmak üzere 3 halk pazarındaki, 10pazar esnafı ve 5 kadın, 5 erkek olmak üzere, 10 alıcı ile yüz yüze derinlemesinemülakat yapılmıştır. Araştırmada olgubilim (fenomenoloji) desenikullanılmıştır. Araştırma verileri, araştırmacıların geliştirdiği yarıyapılandırılmış görüşme formu aracılığıyla elde edilmiştir. Araştırmasonucunda; satıcıların, alıcıları çekmek için, tezgâhın düzenine, iletişimlerine, dış görünüşlerine ve davranışlarına dikkat ettikleri tespit edilmiştir.Pazarda ürün çeşitliliğinin fazla olması, ürünlerin taze ve ucuz olması, pazarlık yapma şansının olması, alıcıların pazarı başlıca tercih etme nedenleriolarak belirlenmiştir. Alıcılar, satıcılardan, çürük ürünleri arayakarıştırmaları, tezgâhın önü ile arkasındaki ürünlerin aynı olmaması gibinedenlerden dolayı şikâyetlerde bulunmuşlardır.
A Qualitative Research on the Behaviours of Dealers and Customers and Mutual Bazaar Strategies Used in the Traditional Bazaar Environment
anemon
Keywords: Bazaar Strategies; Qualitative Research; Phenomenology; Traditional Bazaar; Dealer; Pazar Stratejileri; Nitel Araştırma; Olgubilim; Halk Pazarı; Pazar Esnafı